EFFECT OF PRIMARY NUTRIENT AND ZINC ON NUTRIENT UPTAKE AND YIELD ATTRIBUTES OF MAIZE ( TTRIBUTES OF MAIZE (ZEA MAYS L.) - KUMAR, OM; DAVID, ARUN A; KUMAR, RAKESH; SANDEEP K. MALYAN, BRIJESH YADAV, (The Bioscan, 2016)
Field experiments were conducted in factorial design with three replications involving 9 treatment combination (three primary nutrient levels: 0, 50 and 100% RDF and zinc levels: 0, 10, and 20 kg/ha) to evaluate the effect of primary nutrient and zinc application on nutrient uptake, growth and yield attribute of maize (Zea mays L.). Results revealed that treatment combination P2 M2 (@ 120 Kg N ha-1 + 60 Kg P2 O5 ha-1 + 40 Kg K2 O ha-1 + @ 20 Kg ZnSO4 ha-1) significantly enhanced the growth and yield attribute, primary nutrient and zinc uptake, over their respective counter treatments. The highest dry weight in P2M2 (360.00 g) and the minimum was recorded in control of (307.33 g). Maximum grain yield (5.95 t ha-1) and stover yield of (13.10 t ha-1) was recorded in P2 M2 followed by P1M1. The highest N, P2O5, K and ZnSO4- uptake by grain (67.54, 10.73, 21.97 Kg ha-1 and 49.67 mg kg ha-1) and stover (43.29, 4.83, 59.319 Kg ha-1and 89.41 mg kg ha-1) was recorded in the treatment combination i.e 120 Kg N ha-1 + 60 Kg P2 O5 ha-1 + 40 Kg K2O ha-1 + @ 20 Kg ZnSO4 ha-1. Treatment P2M2 was found to be the best.